THE ADVANTEGEOUS VALUES OF CODE-SWITCHING IN INDONESIAN EFL TEACHING-LEARNING CONTEXTS - Kristian Florensio Wijaya (UC Journal: ELT, Linguistics and Literature Journal, 2021)
Code-switching had been one of the central discussed educational topics forming in both globalized and Indonesian EFL learning contexts. On the first supportive side, the further utilization of code-switching is cogently supported by Indonesian EFL teachers to better facilitate the whole second language learning dynamics. Taking a glance on another contradictory side, the use of code-switching is strongly discouraged to maximize learners’ target language competencies in a meaningful manner. This qualitative study employed a document analysis approach to proffer the advantageous values potentially imparted by the incorporation of code-switching through Indonesian EFL learning settings. Thirty code-switching studies conducted in this archipelago were carefully selected to generate more robust research findings. Two major themes were unearthed in this study namely code-switching potentially promote more meaningful L2 learning encounters and lead Indonesian EFL learners to foster their target language competencies to the fullest potentials. Regarding the future advancement of code-switching studies in this nation, the researcher expectantly hoped future researchers will conduct more exhaustive library qualitative investigations focusing on the disadvantages of code-switching to provide richer perspectives toward this L2 communication strategy.